Klasifikasi Kualitas Jagung Terhadap Data Percobaan Penanaman dengan Metode Decision Tree - Tomy Nanda Putra; Darmansah Darmansah; M Yoka Fathoni (STMIK Budi Darma, 2023)
Corn is one type of plant that is widely cultivated in Indonesia because it has a high enough price, especially the need for this plant. This plant is used as a substitute for carbohydrates and protein after rice, is also used as feed ingredients for livestock. This lack of corn production is caused by several factors such as the age of trees, fertilizers and pests. The impact that occurred was a decrease in corn production at a time when there were many needs of the company and the community would corn. The corn data processed in this study were sourced from the Department of Horticultural Food of Pasaman Regency and the owners of corn crops. Furthermore, the data is processed using the Rapid Miner software. Aimed to find out the prediction of the quality of the corn planting experiment. The method used in solving this problem is C4.5 Algorithm. From the testing of this method, it was found that two predictions in corn cultivation were ‘good and‘ not good. This analysis makes it easier for farmers to plant corn, especially in the selection of seeds to fertilize them so as to produce good fruit for consumption